Differences in fatty acids, zinc, and copper profiles among processed Kedawung (Parkia roxburghii G. Don) products and their relevance to cardiovascular health - Komang Gde Ardi Pradnya Septiawan; Gemala Anjani; Aryu Candra; Ahmad Syauqy; Zulfatul Masruroh (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2026)
ABSTRACTBackground: Kedawung is an underutilized legume which are known for its nutrient-rich qualities that can improve through various processing methods, including fermentation and flouring. Nutrients such as fatty acids, zinc, and copper play important roles in lipid metabolism and antioxidant defense and there are therefore relevant to cardiovascular health.Objective: This study aimed to examine differences in fatty acid, zinc, and copper profiles among three processed Kedawung products boiled Kedawung seeds (BK), Kedawung tempeh (TK), and Kedawung tempeh flour (TPK) and to evaluate their potential relevance to cardiovascular health.Materials and Methods: The study employed gas chromatography to analyze fatty acids and atomic absorption spectrophotometry to analyze zinc and copper in BK, TK, TPK samples. A normality test was conducted using Shapiro-Wilk, followed by one-way ANOVA or Kruskal–Wallis tests for normally and non-normally distributed data, respectively.Results: The highest total fatty acid content was observed in TK (97.965 ± 12.002 %w/w), while TPK showed the lowest value (38.144 ± 29.677 %w/w). BK contained seven types of fatty acids, TK contained six, and TPK contained three. Stearic acid, linoleic acid, and lignoceric acid were present in all three samples. Zinc and copper contents were highest in TPK (62.529±8.0205 ppm and 17.987±4.097 ppm) and lowest in TK (12.854±2.065 ppm and 2.639±0.080 ppm).Conclusion: Different processing methods significantly influence the fatty acid, zinc, and copper profiles of Kedawung. Processed Kedawung products present nutritional characteristics with potential relevance to cardiovascular health, although further studies are required to confirm their functional effects.Keywords: Copper; fatty acid; food processing; kedawung; zinc